The CZTS Thin Films Grown by Sulfurization of Electrodeposited Metallic Precursors: The Effect of Increasing Tin Content of the Metallic Precursors on the Structure, Morphology and Optical Properties of the Thin Films - E.A. Botchway; Francis Kofi Ampong; Isaac Nkrumah; D.B. Puzer; Robert Kwame Nkum; Francis Boakye (East European Journal of Physics, 2023)
A study has been carried out to investigate the influence of the amount of Sn in the precursor solution, on some physical properties of CZTS films grown by sulfurization of electrodeposited metallic precursors. The growth of the CZTS samples was achieved by sequential electrodepositon of constituent metallic layers on ITO glass substrates using a 3-electrode electrochemical cell with graphite as a counter electrode and Ag/AgCl as the reference electrode. The Sn-content in the metallic precursor was varied by varying the deposition time of Sn. The stacked elemental layer was then soft annealed in Argon at 350 °C, and subsequently sulfurized at 550° C to grow the CZTS thin films. The structure, morphology and optical properties were investigated. X-ray diffraction studies revealed that, irrespective of the Sn content all the films were polycrystalline and exhibited the Kesterite CZTS structure with preferred orientation along the (112) plane. However, there was an increase in the amount of peaks indexed to the undesirable secondary phases, as the Sn content in metallic precursor was increased. Optical absorption measurements revealed the existence of a direct transition with band gap values decreasing from 1.74 eV to 1.25 eV with increasing amounts of Sn. The lower value for the band gap was attributed to the presence of secondary phases formed in addition to the CZTS film. Morphology of the sulfurized films showed a compact and rocky texture with good coverage across the entire substrate. However, CZTS films with a higher Sn content appeared to have a molten metallic surface with deep cracks which could have adverse effects on the electrical properties of the film. EDAX analysis showed all the films were consistent with the formation of CZTS. It is evident from all the characterization techniques that increasing the Sn content of the stacked metallic precursors beyond stoichiometric amounts had an adverse effect on the structural and optical properties of CZTS films grown by this technique.